Formulation and Evaluation of Solid Lipid Nanoparticles of Quetiapine Fumarate and Quetiapine Hemifumarate for Brain Delivery in Rat Model - Shikha, Lohan; Sumit, Sharma; Ramachandra Murthy, Rayasa (Pharmaceutical Nanotechnology, 2013)
Quatiepine, an effective atypical anti psychotic administered as fumarate or hemifumarate salts by intravenous injection shows poor brain uptake due to low partitioning and/or Pgp efflux. In order to improve their brain availability, solid lipid nanoparticles (SLN) loaded with Quetiapine fumarate or hemifumarate were prepared using glyceryl monostearate (GMS), poloxamer 407 and hydrogenated soya phosphatidylcholine (HSPC) as stabilizers—using a hot melt emulsification high- pressure homogenization technique. They were characterized for physical characteristics like particle size, polydispersity (PDI), shape and entrapment efficiency (EE). Fomulation and process parameters were optimized based on particle size, PDI and EE. SLNs with a mean particle size of 101.1 nm were obtained for quetiapine fumarate and 93.6 nm for quetiapine hemifumarate. In-vitro drug release study showed the release followed Higuchi kinetics model for both the formulations. In-vivo studies showed a significant increase in the percentage of drug reaching the brain when administered in the form of SLN’s as compared to the respective drug solutions and the increase was greater in case of quetiapine hemifumarate salt.
Keywords: Brain delivery